2011
DOI: 10.1002/da.20835
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of Internet-delivered cognitive behavioral therapy for posttraumatic stress disorder

Abstract: Results provide preliminary support for Internet-based CBT as an efficacious treatment for individuals with a confirmed primary diagnosis of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 53 publications
4
115
1
1
Order By: Relevance
“…Dropout rates from the study were comparable to previous trials of internet-based guided self-help for PTSD (Spence 2011, Ivarsson, Blom et al 2014) and other mental disorders (Spek, Cuijpers et al 2007). They were also of a similar magnitude to dropout from therapist-administered therapy ).…”
Section: Comparison To Other Studiessupporting
confidence: 73%
See 2 more Smart Citations
“…Dropout rates from the study were comparable to previous trials of internet-based guided self-help for PTSD (Spence 2011, Ivarsson, Blom et al 2014) and other mental disorders (Spek, Cuijpers et al 2007). They were also of a similar magnitude to dropout from therapist-administered therapy ).…”
Section: Comparison To Other Studiessupporting
confidence: 73%
“…In agreement with the findings of recent meta-analyses of internet-based self-help for PTSD, the intervention was found to be effective in comparison to waitlist (Kuester, Niemeyer et al 2016, Sijbrandij, Kunovski et al 2016, with the magnitude of effect lying at the higher end of the effect sizes reported by these reviews. The effect size was larger than that reported previously for internet-based CBT for clinical populations of PTSD sufferers (Spence 2011, Ivarsson, Blom et al 2014), which may be influenced by the fact that the intervention was systematically developed through an iterative process of modelling and pilot testing intended to create an optimally effective programme . The programme had a greater trauma-focus and emphasis on imaginal exposure work via writing and reading a narrative, than other internet-based CBT programmes for PTSD.…”
Section: Comparison To Other Studiesmentioning
confidence: 59%
See 1 more Smart Citation
“…Between-group effects were analysed using univariate analysis of covariance (ANCOVA) while controlling for pre-treatment scores as a covariate (Vickers & Altman 2001). According to Cohen's standards for research in the behavioural sciences, an ES d≥0.80 between-group for treatment effects in psychotherapy is considered large, d=0.80-0.5 moderate, and d=0.50-0.20 small (Spence et al 2011). Clinical relevance was counted as a change in prevalence of DSM-IV disorders based on the results from the MINI interviews at inclusion and at post-treatment follow up.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For example, more than 10 randomised controlled trials (RCTs) have reported the clinical benefi ts of iPT for clinical and subclinical depression Perini, Titov, & Andrews, 2009;Ruwaard et al, 2009;Titov, Andrews, Davies, et al, 2010), social phobia (Andersson et al, 2006;Berger, Hohl, & Caspar, 2009;Botella et al, 2010;Carlbring et al, 2007;, and panic disorder Klein et al, 2009;Wims, Titov, Andrews, & Choi, 2010). Encouraging evidence has also been found from a smaller but rapidly growing number of RCTs or open trials evaluating iPT for generalised anxiety disorder Robinson et al, 2010;, obsessive compulsive disorder Andersson et al, 2012;Wootton et al, 2011), and post-traumatic stress disorder (Klein et al, 2010;Spence et al, 2011).…”
Section: Internet-delivered Psychological Interventionsmentioning
confidence: 99%